Some Insults are Easier to Detect: The Embodied Insult Detection Effect - Wellsby, Michele; Siakaluk, Paul D.; Pexman, Penny M.; Owen, William J. (Frontiers in Psychology, 2010)
In the present research we examined the effects of bodily experience on processing of insults in a series of semantic categorization tasks we call insult detection tasks (i.e., participants decided whether presented stimuli were insults or not). Two types of insults were used: more embodied insults (e.g., asswipe, ugly), and less embodied insults (e.g., cheapskate, twit), as well as non-insults. In Experiments 1 and 2 the non-insults did not form a single, coherent category (e.g., airbase, polka), whereas in Experiment 3 all the non-insults were compliments (e.g., eyeful, honest). Regardless of type of non-insult used, we observed facilitatory embodied insult effects such that more embodied insults were responded to faster and recalled more often than less embodied insults. In Experiment 4 we used a larger set of insults as stimuli, which allowed hierarchical multiple regression analyses. These analyses revealed that bodily experience ratings accounted for a significant amount of unique response latency, response error, and recall variability for responses to insults, even with several other predictor variables (e.g., frequency, offensiveness, imageability) included in the analyses: responses were faster and more accurate, and there was greater recall for relatively more embodied insults. These results demonstrate that conceptual knowledge of insults is grounded in knowledge gained through bodily experience.